Comparing Architectural Styles for Service-oriented Architectures – a REST vs. SOAP case study - Becker, Jörg; Matzner, Martin; Oliver, Müller (Proceedings of the Information Systems Development Conference 2008, 2008)
Two architectural styles are currently heavily discussed regarding the design of service-oriented architectures (SOA). Within this chapter, we have compared those two alternative styles - the SOAP-style with procedural designs similar to remote procedure calls and the REST-style with loosely coupled services similar to resources of the World Wide Web. We introduce the case of a business network consisting of manufacturers and service providers of the electronics industry for deriving a set of requirements towards a specific SOA implementation. For each architectural style, we present a concrete SOA design and evaluate it against the defined set of requirements.
Keywords: Service-oriented architecture; REST; SOAP